PENGARUH CAR DAN NPF TERHADAP ROA PADA PT.BANK NTB SYARIAH TAHUN 2018-2024 - Fatiha, Nur; M. Wakhid Mustofa (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research investigates the impact of the Capital Adequacy Ratio (CAR) and Non-Performing Financing (NPF) on the Return on Assets (ROA) of PT Bank NTB Syariah over the period 2018–2024. The study applies a quantitative method utilizing multiple linear regression analysis based on secondary data sourced from the bank’s official financial reports. The findings reveal that CAR exerts a significantly positive influence on ROA, while NPF has no significant relationship with it. When analyzed together, CAR and NPF were also found to have no joint significant effect on ROA, implying that additional factors such as operational efficiency might play a role in determining profitability. These results highlight the crucial role of effective capital management in enhancing the financial performance of Islamic banks following their conversion to the Sharia system. Moreover, this study extends the body of knowledge on Islamic finance by providing new insights within the context of regional Islamic banking institutions.